EFEKTIVITAS GAME EDUKATIF TERHADAP KEMAMPUAN MENULIS PERMULAAN ANAK AUTIS DI SEKOLAH DASAR - DINA EFFENDI, SITI (Jurnal Pendidikan Khusus, 2017)
Abstract:This research is grounded by the barriers of the ability to write the beginning include writing alphabets, writing syllables and writing words. So it need to be given a game that can attract attention as well as to train the ability to write the beginning of the child. An educative game is a game played on PC / tablet / android for improving write the beginning using a pen stylus that has the same function as a pencil or pen. Aspects developed in this research, the child is able to write alphabets, write syllables and write words.The research method in this research is by using quantitative research approaches to study the type of Single Subject Research (SSR), and the design of A (Baseline) - B (Intervention). Subjects in this study is one child with autism by age 7 years the SDN Percobaan Surabaya, the purpose of this research is to prove the effect of educative game on the ability to write the beginning of children with autism in SDN Percobaan Surabaya. Technique of collecting data by observation and documentation (observation of baseline A and B phase instrument observation instrument), while data analysis technique analyze data using simple descriptive statistic technique that is visual analysis covering analysis between condition and condition. The results showed that the baseline phase (A) was conducted for 5 sessions with the results as much as 40-46 times the frequency range and the intervention phase (B) by treatment using educational games conducted for 7 sessions with the results of the frequency range of 48-56 times. Each meeting is held for 20 minutes. Changing trend directions in the baseline phase (A) to the intervention phase (B) is decreased and then increased, the percentage of overlap of data showing the data by 0%, this indicates the target behavior intervention effect on the ability to write the beginning of the subject A, which means their influence educational games on the ability to write the beginning of children with autism in SDN Percobaan Surabaya. . Keywords: Educative Game, Write The Beginning